2006
DOI: 10.1074/jbc.m509770200
|View full text |Cite
|
Sign up to set email alerts
|

Signal-dependent Control of Gluconeogenic Key Enzyme Genes through Coactivator-associated Arginine Methyltransferase 1

Abstract: Together with impaired glucose uptake in skeletal muscle, elevated hepatic gluconeogenesis is largely responsible for the hyperglycemic phenotype in type II diabetic patients. Intracellular glucocorticoid and cyclic adenosine monophosphate (cAMP)/protein kinase A-dependent signaling pathways contribute to aberrant hepatic glucose production through the induction of gluconeogenic enzyme gene expression. Here we show that the coactivator-associated arginine methyltransferase 1 (CARM1) is required for cAMP-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
2
27
1
2
Order By: Relevance
“…In addition to effects of PRMT5, the type I PRMT family member PRMT4/coactivator-associated arginine methyltransferase 1 (CARM1) has also been found to promote gluconeogenic gene expression via an interaction with CREB and through subsequent increases in H3 methylation (15). Indeed, we have also detected increases in asymmetric H3R8me2 amounts at CREBbinding sites, potentially catalyzed by the type I enzyme PRMT2, in response to glucagon simulation.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to effects of PRMT5, the type I PRMT family member PRMT4/coactivator-associated arginine methyltransferase 1 (CARM1) has also been found to promote gluconeogenic gene expression via an interaction with CREB and through subsequent increases in H3 methylation (15). Indeed, we have also detected increases in asymmetric H3R8me2 amounts at CREBbinding sites, potentially catalyzed by the type I enzyme PRMT2, in response to glucagon simulation.…”
Section: Discussionsupporting
confidence: 54%
“…The methyltransferase PRMT1 is known to increase activity of transcription factors involved in glucose homeostasis (13)(14)(15). Whereas previous results have implicated CARM1 (PRMT4) in the regulation of G6PC (16), the present study found that knockdown of PRMT1 reduced G6PC expression, suggesting that PRMT1 also participates in the transcriptional regulation of this gluconeogenic gene. This strengthens the association between ADMA-producing co-activators and gluconeogenic enzyme expression.…”
Section: Discussioncontrasting
confidence: 51%
“…SAM and SAH levels as well as protein-arginine methylation are altered in diabetic models (5-9) and in humans (10, 11). Gluconeogenic enzyme expression, responsible for hepatic glucose production and hyperglycemia in diabetics, is dependent upon methyltransferases (16). Human subjects with insulin resistance and non-alcoholic steatohepatitis have reduced capacity for transmethylation of methionine (11), and the capacity for methylation is related to insulin resistance and metabolic syndrome (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have implicated CARM1 as a regulator of cellular metabolism [5,[66][67][68][69]. CARM1 was shown to be a co-activator of PPARγ [5], a key transcription factor regulating glucose and lipid metabolism.…”
Section: Carm1 O-glcnacylation May Be a Sensor Of Cellular Stress Andmentioning
confidence: 99%